EVALUATION OF HAEMATOBIOCHEMICAL AND CARDIOPULMONARY PARAMETERS IN GOATS UNDERGOING ORTHOPEDIC SURGERY USING TOTAL INTRAVENOUS ANAESTHESIA - Abdul Asim Farooq; Muhammad Arif Khan; Hamid Akbar; Muhammad Ashraf; Saeed Murtaza; Maqbool Hussain Shah; Muhammad Usman; Muhammaad Arshad Javid (Journal of Animal and Plant Sciences, 2023)
This research was done to identify the usefulness of clinico-physiological and haematobiochemical effects of total intravenous anaesthesia affected by combination of diazepam-propofol-ketamine with constant rate of infusion in goats undergoing orthopedic surgery (bone plating). Five goats having metatarsal and metacarpal fracture were included in the study. The animals were sedated with diazepam @ 0.25 mg/kg inducted with ketamine and propofol at the dose rate of 2.0 mg/kg each and maintained with diazepam, ketamine and propofol at the dose rate of 0.02 mg/kg/hr, 2.40 mg/kg/hr and 0.96 mg/kg/hr, respectively after using volumetric syringe driving pump. The clinico-physiological and haematobiochemical parameters of above said animals were recorded at 0 min before sedation (baseline), 1, 5, 10, 15, 20, 30, 60 and 120 minutes after induction of anaesthesia (Indoor Surgery Clinic, Department of Veterinary Surgery, University of Veterinary and Animal Sciences Lahore, Pakistan). A score of (1.00±0.00) for the anesthetic parameters was observed, indicating a smooth induction, good muscular relaxation, and easy recovery at various time intervals following therapy compared to baseline before induction: the heart rate, respiration rate, rectal temperature, blood pressure, and oxygen haemoglobin saturation were substantially different (p<0.05). Throughout the observation period, there were non-significant differences in the packed cell volume, haemoglobin concentration, leukocyte, granulocyte, lymphocyte, and monocyte counts (p>0.05). At various points during the observation period: the levels of serum glucose, alanine aminotransferase, aspartate aminotransferase, and cortisol varied considerably (p>0.05) in comparison to 0 minutes (the baseline) prior to the induction of anesthesia. It was determined that goats underwent complete intravenous anaesthesia caused by a mixture of diazepam, propofol, and ketamine.
Keywords: Anaesthesia; small ruminants; constant rate infusion; bone platting